Overview on the heavy metal toxicity mechanisms and the role of alimentary factors in detoxification - A.N. Aralbaeva; G.A. Yeszhanova; A.N. Aralbayev; G.T. Zhamanbayeva; N.I. Zhaparkulova; A.I. Zhussupova; M.K. Murzakhmetova (International Journal of Biology and Chemistry, 2024)
People are continuously subject to various environmental and chemical pollutants originating from industrial and agricultural activities. Heavy metals can be identified as aseparate group of xenobiotics that pose a danger to human health. They affect almost all body systems, exerting toxic, allergic,carcinogenic, and gonadotropic effects. The toxicity of heavy metals to the body, their neutralization and elimination from the body depends on several factors, including nutritional status, as there are detoxification mechanisms in the human body, which require the intakeof certain nutritional compounds. The quality of nutrition directly affects the state of the body since the essentialcompounds are mostly obtained from the food. Consumption of nutritional compounds is a significant factor that determines human health, growth, development, physical and mental activities and promotes more effective recovery during illness. The use of knowledge on the intoxication mechanisms and the role of alimentary factors in the body detox contribute to a deeper understanding of the processes in the development of the ways to neutralize the negative effects of various toxic compounds. At the same time, a large number of articles and reviews are devoted to the study and analysis of the manifestation of toxic effects of heavy metal compounds, mechanisms of their transformation in the environment, as well as damaging effects on the body systems; articles devoted to the study of the neutralization of the poisoning effect of various xenobiotics are aimed at investigating the detoxification effect of finished dosage forms. The importance of examining how nutritional factors like proteins, probiotics, vitamins, and dietary fiber contribute to the body detoxification processes is significant. This review analyses literature data of scientists from Kazakhstan, far and near abroad on the mechanisms of toxicity of a wide range of heavy metals, as well as the role of key nutrients in the process of their detoxification.